2010
DOI: 10.1021/jf103347p
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Endogenous Protein Disulfide Isomerase Family Proteins and Glutenin Macropolymer

Abstract: The effects of endogenous protein disulfide isomerase (PDI) family proteins on the properties of gluten proteins in dough during breadmaking were determined using bacitracin, an inhibitor of PDI. Bread loaf volume in the presence of bacitracin was increased to 118% of that in the absence of bacitracin. The addition of bacitracin caused a decrease in the extension tolerance of the dough. The amount of sodium dodecyl sulfate (SDS)-insoluble glutenin macropolymer (GMP) in dough decreased to approximately 70% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
(59 reference statements)
0
11
0
1
Order By: Relevance
“…Because wheat flour arises from milled starchy endosperm, the five groups of PDI family proteins must be present in flour (Table 4). We previously detected oxidative refolding activity in an extract from wheat flour, and its activity was inhibited by the PDI inhibitor bacitracin [66]. Therefore, PDI family proteins may be active in both the starchy endosperm of the dry mature grain and flour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because wheat flour arises from milled starchy endosperm, the five groups of PDI family proteins must be present in flour (Table 4). We previously detected oxidative refolding activity in an extract from wheat flour, and its activity was inhibited by the PDI inhibitor bacitracin [66]. Therefore, PDI family proteins may be active in both the starchy endosperm of the dry mature grain and flour.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PDI family proteins may affect the quality of food products. We previously demonstrated that PDI family proteins play a role in retaining glutenin macropolymers during dough mixing, and these polymers are the most important factor for dough’s tensile strength [66]. We semi-quantitatively analyzed the levels of the five PDI family protein groups in a wheat flour sample (Table 4) and found that among the five groups of PDI family proteins, TaPDIL1 levels were the highest.…”
Section: Resultsmentioning
confidence: 99%
“…The most thoroughly characterized to date involves oxidation of substrate proteins by protein disulfide isomerase (PDI), which is in turn oxidized by the endoplasmic reticulum oxidase Ero1, which was first identified in yeast (Frand and Kaiser, ; Pollard et al ., ). It has recently been shown that plant homologues of Ero1 and PDI are also involved in storage protein deposition in rice (Onda et al ., , ; Satoh‐Cruz et al ., ), and that PDI plays an important role in glutenin polymerization during the breadmaking process (Koh et al ., ). However, the pathways that mediate disulfide bond formation within the plant ER have not been characterized in detail.…”
Section: Introductionmentioning
confidence: 97%
“…LMW-GS are encoded by Glu-A3, Glu-B3 and Glu-D3 loci on the short arms of group 1 chromosomes (GUPTA and SHEPHERD, 1990), which are further divided into B-, C-and D-group subunits according to their mobilities in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (D'OVIDIO and MASCI, 2004). HMW-GS contain 4-7 cysteine residues and LMW-GS have six conserved cysteine residues and one or more additional cysteine residues (KOH et al, 2010). Most of these residues form intrachain disulfide bonds, whereas some of these residues form interchain disulfide bonds to form GMPs (ORSI, 2001).…”
Section: Introductionmentioning
confidence: 99%